Proceso de exportación para la empresa Inspa. Cía. Ltda. que comercializa balanceado de tilapia, en la provincia de El Oro - Ortega Monserrate, Hans Enrique (2015)
This paper whose research I conducted, focuses on finding possible needs requiring Inspa Cia. Ltda. , Whose problem today is open or take the field as an exporter balanced, which external factor that influences is the competition and especially the economic environment with neighboring Peru , is why considering all these factors has objected to establish an export plan where the same process and procedure is demonstrated. This integrative and research work is mainly based on known scientific journal articles and papers, whose foundation helped me to help solve problems and give a guideline to follow in order to focus on this issue and the analysis of barriers and obstacles may arise in the company in international negotiations .